SolidWorks Flow Simulation: Selecting the optimal mesh for conducting CFD analysis on a centrifugal fan - Salmat, Salmat; Yanti Sari, Delima; Fernanda, Yolli; Prasetya, Febri (Researcher and Lecturer Society, 2023)
The accuracy of mesh use determines the suitability of simulation results with experimental test results, therefore it is necessary to study the type and number of mesh used for flow simulation. This study aims to investigate the type of mesh and the number of cells that are appropriately used in the simulation of centrifugal fans using the Solidworks Flow Simulation module. The research was conducted by comparing the simulation results with the experimental results on centrifugal fans that have been carried out by previous studies. In this research, the type of mesh used is global mesh. The parameter of determining the number of cells is done by varying the mesh level because the mesh level affects the number of cells. In this simulation study, the boundary condition is set to one flow volume of 5 m3/h and a rotation speed of 92.362 rad/s. In this study, the total pressure and efficiency of the centrifugal fan are the things that are seen from the comparison of flow simulation with the experiment. Based on the simulation results that have been carried out, mesh levels 1 to 4 show results that differ significantly from the experimental results. At machine levels 5 to 7, the results are close to the experimental results, but the closest total pressure and efficiency values are at mesh level 5. The results of this study can be a reference for research that simulates centrifugal fans.